Fault-Tolerant inverter for Power Flow Control in Variable-Speed Four-Wire Permanent-Magnet Generators - Catuogno, Guillermo Ricardo (2015)
A strategy for fault detection and tolerance on the inverter that controls power flow in variable-speed permanent-magnet generators is proposed in this paper. The performance of the proposed strategy is analyzed in two different four-wire topologies. In the first topology, the neutral point of the generator is connected to the middle point of the dc-link capacitor bank, whereas in the second topology, it is connected to a fourth leg of the inverter. The main contribution of this paper resides in the control scheme, which allows a steady operation through a fault occurrence without the need of reconfiguring neither the inverter topology nor the control algorithm. In this way, transients and the use of extra hardware components are avoided. In addition, a control loop that allows limiting the generator losses at any operation point is presented in order to protect the machine. Finally, experimental results, obtained from a laboratory prototype, validate the practical feasibility of the proposed strategy.